Penerapan Supervisi Klinis dalam Meningkatkan Kemampuan Mengajar Guru Matematika SMP Plus Ibadurrahman - Ahmad Fahrudin (Jurnal Ilmiah Wahana Pendidikan, 2019)
The basis of this research is to determine the ability of several teachers, especially mathematics teachers at SMP Plus IBADURRAHMAN, who are known to be lacking in the use of learning media. Based on the results of the evaluation of the two types of test kits prepared by the teacher, it can be seen that the average value of the two types of instruments is 38 and 40 which consists of making learning media and participating in training. The purpose of this study is to improve the ability of teachers in developing learning media, so that the desired learning objectives are in accordance with the lesson plan. This study was conducted as part of the cycle assessment process. The subjects of this study were mathematics teachers with less than 5 years of teaching experience with a total of 3 teachers. Meanwhile, the purpose of this research activity is to improve the ability of teachers in developing learning media. Based on the research results, the ability of teachers to develop learning media can be improved through the application of clinical supervision. There is an increase in the ability to develop more interesting learning media. And the application of clinical supervision has been proven to increase teachers' interest in the use of learning media, especially the value of teachers' teaching abilities by increasing the use of learning media in cycles 39 to 41.7.